KONSEP KETAHANAN KELUARGA DALAM ISLAM - Amatul Jadidah amatul (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
Islam pays its great attention towards family life by putting the fundamental sources of familyhood in daily life activities. These fundamental sources have to be emphasized in some form of aspects such as educational aspect, biological, religious, caring, social, economic, and entertaining aspect. Family life qualities certainly depend on the relation with the society. These qualities literally influenced the environment and people in general, moreover for the citizen. Family becomes the medium for individual to sprout over of mental caring and sustainability. Family’s sustainability constitutes of the mediums to comprehend the family’s member accomplishments. Each individual must be measured by its aspect on the roles, function, and responsibility to create prosperity. Ideal family sustainability can be measured by its tenacity towards structural changes, functions, and communication as well. Thus, this family sustainability aspects can be defined into five: religion, physical, mental, economic, and sosial sustainability. This is the main aspect in the familyhood. Almost out of the question for Indonesia to be able to compete in the future when the family sustainability is neglected